Interaction of lipids with the neurotensin receptor 1 - Bolivar, J; Muñoz-García, J; Castro-Dopico, T; Dijkman, P; Stansfeld, P; Watts, A (Elsevier, 2016)
Information about lipid–protein interactions for G protein-coupled receptors (GPCRs) is scarce. Here, we use electron spin resonance (ESR) and spin-labelled lipids to study lipid interactions with the rat neurotensin receptor 1 (NTS1). A fusion protein containing rat NTS1 fully able to bind its ligand neurotensin was reconstituted into phosphatidylcholine (PC) bilayers at specific lipid:protein molar ratios. The fraction of motionally restricted lipids in the range of 40:1 to 80:1 lipids per receptor suggested an oligomeric state of the protein, and the result was unaffected by increasing the hydrophobic thickness of the lipid bilayer from C-18 to C-20 or C-22 chain length PC membranes. Comparison of the ESR spectra of different spin-labelled lipids allowed direct measurement of lipid binding constants relative to PC (Kr), with spin-labelled phosphatidylethanolamine (PESL), phosphatidylserine (PSSL), stearic acid (SASL), and a spin labelled cholesterol analogue (CSL) Kr values of 1.05 ± 0.05, 1.92 ± 0.08, 5.20 ± 0.51 and 0.91 ± 0.19, respectively. The results contrast with those from rhodopsin, the only other GPCR studied this way, which has no selectivity for the lipids analysed here. Molecular dynamics simulations of NTS1 in bilayers are in agreement with the ESR data, and point to sites in the receptor where PS could interact with higher affinity. Lipid selectivity could be necessary for regulation of ligand binding, oligomerisation and/or G protein activation processes. Our results provide insight into the potential modulatory mechanisms that lipids can exert on GPCRs.